Library usage patterns of the Pangasinan State University, Bayambang Campus as affected by students' personal attributes, library resources, facilities and services - Iglesias, Blesilda Q. (1994)
This is an analysis of the library usage patterns of the students of Pangasinan State University, Bayambang Campus. The objectives of the study are: 1) To determine the relationship between the personal attributes of the students and their library usage pattern; 2) To determine the status of the resources, facilities and services of the PSU Bayambang Campus Library as assessed by the students.